Efektivitas Penggunaan Media Pembelajaran Hologram Video pada Materi Geometri Bangun Ruang Sisi Datar di SMP Negeri 2 Alla - Awi; Ilham Minggi; Ermayanti (Issues in Mathematics Education (IMED), 2023)
This pre-experimental research aimed to determine the effectiveness of using Hologram Videolearning media for geometry materials. The experimental unit in this study consisted of one class of gradeIX students of SMP Negeri 2 Alla. The sample of this study was grade IX D students. This research wascarried out for five meetings where one meeting for pretest, one meeting was for posttest, and three meetingsfor learning session using Hologram Video learning media. Data were collected using observation sheets,learning achievement tests, and students’ response questionnaire. The data were analyzed using descriptiveand inferential statistical analysis. The results indicated that: (1) students' mathematics learningachievements is 79.896 (exceeding the KKM) of the ideal score of 100; (2) the average value of normalizedgain inferentially is more than 0.3, namely 0.737 which is in the high category; (3) the classical masterylevel of students is inferentially less than 85%, which is 70.83%; (4) the average percentage of students’activities in learning is 85.78% or it is in the active category; (5) the average percentage of students’responses is 89.58% or it is in the very positive category. Thus, it can be concluded that the use of HologramVideo learning media is effective for geometry materials if it is viewed from learning achievement, students’activities, and students’ responses. It is because all indicators meet the effectiveness criteria.